190. IMPLEMENTATION OF THE ESOPHAGECTOMY COMPLICATIONS CONSENSUS GROUP DEFINITIONS: THE BENEFITS OF SPEAKING THE SAME LANGUAGE. (24th September 2022) - Muir, Duncan; Antonowicz, Stefan; Whiting, Jack; Low, Donald; Maynard, Nick
Abstract: In 2015 the Esophagectomy Complications Consensus Group (ECCG) reported consensus definitions for complications after oesophagectomy. This aimed to reduce variation in complication reporting, attributed to heterogeneous definitions. This systematic review aimed to describe the implementation of this definition-set, including the effect on complication frequency and variation. A systematic literature review was performed, identifying all observational and randomised studies reporting complication frequencies after oesophagectomy since the ECCG publication. Recruitment periods before and subsequent to the index ECCG publication date were included. Coefficients of variance were calculated to assess outcome heterogeneity. Study quality was assessed using the Newcastle-Ottawa score. Of 144 studies which met inclusion criteria, 70 (48.6%) used ECCG definitions. The median number of separately reported complication types was five per study; only one study reported all ECCG complications. The coefficients of variance of the reported frequencies of eight of the ten most common complications was reduced in ECCG adopting studies vs non-adopting studies (p = 0.036) (see Figure 1). Among ECCG studies, the frequencies of post-operative pneumothorax, re-intubation and pulmonary emboli were reduced in 2020–2021, compared to 2015–2019 (p = 0.006, 0.034 and 0.037 respectively). There was no difference in the quality of ECCG adopting studies and non-adopting studies. The ECCG definition-set has reduced variation in oesophagectomy morbidity reporting. This adds greater confidence to the observed gradual improvement in outcomes with time, and its ongoing use and wider dissemination should be encouraged. However, only a handful of outcomes are widely reported, and only rarely is it used in its entirety.